2022
DOI: 10.1038/s41598-022-06685-8
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of Th1 and Th2 cytokine profiles differentiating tuberculous from malignant pleural effusion

Abstract: To clarify the predominance of Th1 or Th2 immune responses in malignant and tuberculous pleural effusion (MPE and TPE, respectively), we performed a meta-analysis of previously published results of the levels of Th1/Th2 cytokines associated with these two types of pleural effusion to evaluate the use of Th1/Th2 cytokine profiles in distinguishing TPE from MPE. We searched the PubMed and EMBASE databases for studies indexed from 2000 to March 2021. We included studies that (a) diagnosed TPE and MPE based on cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Th1 cytokines include IFN-γ, TNF-α, and IL-2, whereas Th2 cytokines are IL-4, IL-5, IL-10, and IL-13. IL-6 defines the Th1/Th2 ratio, which inhibits Th1 differentiation and promotes Th2 induction [ 64 ]. According to our results ( Table 2 ), SPalf2-453 is a mild inducer of IL-2, IFN-γ, IL-4, and IL-13, which might result in balanced rather than biased Th1/Th2-associated responses.…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cytokines include IFN-γ, TNF-α, and IL-2, whereas Th2 cytokines are IL-4, IL-5, IL-10, and IL-13. IL-6 defines the Th1/Th2 ratio, which inhibits Th1 differentiation and promotes Th2 induction [ 64 ]. According to our results ( Table 2 ), SPalf2-453 is a mild inducer of IL-2, IFN-γ, IL-4, and IL-13, which might result in balanced rather than biased Th1/Th2-associated responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that among patients with tuberculous pleurisy, those exhibiting pleural effusion also show higher levels of IL-4 than those with no pleural effusion, while higher levels of IL-4 may result in residual pleural thickening in patients. [ 16 ] The study showed that the expression of interferon-γ in experimental mice was increased during early infection with Mycobacterium TB, while the formation of IL-4 was increased in the course of the chronic infection stage signified by progressive fibrosis and necrotic cavities. [ 64 ] Prior research has documented no differences in serum IL-4 levels between individuals with active pulmonary TB and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relationship between IL-4 levels and TB needs to be verified through observational studies. Zeng et al [ 16 ] conducted a meta-analysis of Th1 and Th2 cytokine profiles to differentiate tuberculous from malignant pleural effusions. However, the main participants of this study were patients with tuberculous pleurisy and malignant pleural effusion.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of caseating granulomata and diffuse pleural inflammation are the hallmarks of TBP [ 20 ]. During this process, multiple Th1 cytokines (especially interferon-gamma [IFN-gamma] and tumour necrosis factor-alpha [TNF-alpha]) are involved, while Th2 cytokines are often suppressed [ 21 ].…”
Section: Pathogenesis For Tuberculous Pleuritismentioning
confidence: 99%